1987
DOI: 10.1111/j.1439-0418.1987.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of flour beetles, Tribolium castaneum (Herbst) (Col., Tenebrionidae) to wheat flour: heritable character or “conditioning”?

Abstract: The majority of adults from 12 laboratory strains of flour beetles (Tribolium castaneum), and a synthetic strain produced by crossing them together, preferred wheat flour when given a choice of 2, 4, or 6 diets (all of which supported survival and reproduction). Sixteen generations of selection on 5 different diets did not alter this behavioral response, which seems to be fixed in Tribolium. Zusammenfassung Über die Anlockung von Mehlkäfern, Tribolium castaneum (Herbst) (Col., Tenebrionidae): Erbliches Verhalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Flour with yeast and pig feed were the next most attractive diets after wheat bran in the olfactometer test. Pig feed is a complex of several components, one of which is yeast, which can increase attractiveness, as confirmed earlier (Bergerson and Wool, 1987). It is noteworthy that bran and coarse wheat meal have the same nutritive components, and yet one was the most and the other the least attractive to T. castaneum adults.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Flour with yeast and pig feed were the next most attractive diets after wheat bran in the olfactometer test. Pig feed is a complex of several components, one of which is yeast, which can increase attractiveness, as confirmed earlier (Bergerson and Wool, 1987). It is noteworthy that bran and coarse wheat meal have the same nutritive components, and yet one was the most and the other the least attractive to T. castaneum adults.…”
supporting
confidence: 64%
“…Different methods of grain processing and other factors that result in grain damage most often increase commodity attractiveness to secondary pests (Freedman et al, 1982;Bergerson and Wool, 1987;Trematerra et al, 2000;Campbell, 2012;Trematerra et al, 2015). For example, Seifelnasr et al (1982) found in an olfactometer test that T. castaneum were significantly more attracted to volatiles of wheat grain parts (endosperm, germ), wheat flour and wheat bran than to the odour of whole wheat grain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was observed in plastic cages (20 × 15 × 8 cm) in which 12 vials were inserted (Bergerson & Wool, 1987). The six experimental diets were randomly assigned to the vials, two replicates of each per cage.…”
Section: Food Preference Behaviormentioning
confidence: 99%
“…Beetles from the six experimental populations, tested repeatedly during the long-term experiment, showed no deviation from this pattern. The majority of beetles always chose the standard medium rather than the food they were reared on (data will be published elsewhere; Bergerson & Wool, 1987).…”
Section: Food-preference Behaviormentioning
confidence: 99%